2015
DOI: 10.17221/591/2014-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

TBARS and microbial growth predicative models of pork sausage stored at different temperatures

Abstract: Kaczmarek A., Cegielska-Radziejewska R., Szablewski T., Zabielski J. (2015): TBARS and microbial growth predicative models of pork sausage stored at different temperatures. Czech J. Food Sci., 33: 320-325.Kinetic models were developed for quality changes of emulsified pork sausages to predict the TBARS (2-thiobarbituric acid reactive substance) and TVC (total viable counts) changes at different temperatures during storage. Kinetic models of TBARS changes with respect to the temperature during storage were deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
6
1
Order By: Relevance
“…An increased TBARS was noticeable for all sausages throughout the refrigerated storage, which indicated that longer storage times could increase the formation of malonaldehyde or other secondary product. At day 0, TBARS of all samples was 0.61 mg MDA/kg sausage, which was lower than the 1.06 mg MDA/kg reported by Kaczmarek et al. (2015) for emulsified pork sausage but higher than the 0.29 mg MDA/kg reported by Tan et al.…”
Section: Resultscontrasting
confidence: 65%
“…An increased TBARS was noticeable for all sausages throughout the refrigerated storage, which indicated that longer storage times could increase the formation of malonaldehyde or other secondary product. At day 0, TBARS of all samples was 0.61 mg MDA/kg sausage, which was lower than the 1.06 mg MDA/kg reported by Kaczmarek et al. (2015) for emulsified pork sausage but higher than the 0.29 mg MDA/kg reported by Tan et al.…”
Section: Resultscontrasting
confidence: 65%
“…Thus, to ensure meat safety through the management of food quality during storage it is important to develop models describing and predicting the quality of the product in a wide range of temperatures. Previously, various mathematical models were implemented to describe the quality indices of food during a storage period [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. The Arrhenius equation was used to predict the temperature dependency of the lipid protein oxidation as well as the microbiological quality of rabbit meat [ 11 , 12 ], pork sausages [ 16 , 18 ], bream fillets [ 19 ], minced beef [ 20 ] and the lipid oxidation of canola and sesame oils [ 14 ] as well as Kilka fish oil [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The definition of aw was performed with a portable high-speed instrument of model AquaLab 3TE with measurement accuracy up to±0,003according to the requirements [39].…”
Section: Discussionmentioning
confidence: 99%